PENGARUH PENDEKATAN PEMBELAJARAN PBL DAN PJBL TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS MAHASISWA PADA MATA KULIAH STATISTIK - Ahmad Nizar Rangkuti; Fitriani Fitriani (Ta'dib, 2019)
This research was conducted at Mathematics Education Study Program at Tarbiyah and Teacher Training Faculties of IAIN Padangsidimpuan at the third semester 2018-2019 academic year. Research method used is quantitative method with bivariate comparative analysis approach aiming to find out the significant differences in students' mathematical communication skills in statistical subjects. The design of this research is a one short case study  comparing the result of two treatments after the post tests. The research was conducted in one classroom, in which one treatment preceding the other treatment with different materials yet contain similar components and difficulties. The result of the research shows that there is significant difference in ability of mathematical communication between problem based learning and project based learning with tcount > ttable: 3,673 > 2,042; in which PjBL is higher than PBL.  In conclusion, PjBL is significantly better than PBL in term of students’ ability in mathematical communication